Identification of Angiotensin Converting Enzyme (ACE) Inhibiting phytochemical Compounds from Aegle marmelos, Euphorbia hirta, Senna auriculata, Ocimum tenuiflorum and Hibiscus rosasinensis by In Silico Analysis - Sanjay Prasad S; Dr. Shanthi priya. S (International Journal of Pharma and Bio Sciences, 2020)
Hypertension is a major health problem which affects about 30% of all adults worldwide. Angiotensin-I converting enzyme (ACE) plays a vital role in the regulation of blood pressure and helps in conversion of angiotensin I into angiotensin II. Inhibiting the ACE activity could reduce blood pressure. As ACE inhibitory drugs can cause adverse side effects, hence, there is a need for the identification of new drugs from natural sources. India has a very long, safe and continuous usage of many herbal drugs and several Indian medicinal plants remains unexplored. Thus, the present study focuses on identifying potent ACE inhibitory compounds from 5 Indian medicinal plants by using AutoDock. We have used AutoDock is used to predict the interaction between macromolecules (protein) with small molecules (ligands) at molecular level. The binding energies of the compounds were compared with the standard drugs Temocapril, Lisinopril, Enalapril and Captopril and the natural compounds showing higher binding energy. The plants selected for the study are Aegle marmelos, Euphorbia hirta, Senna auriculata, Ocimum tenuiflorum and Hibiscus rosa sinensis. Total of 32 phytochemical compounds were identified from the KNApSAck database. From the analysis, three significant compounds β-amyrin (-10.6Kcal/mol), Taraxerol (-9.94Kcal/mol) and Lupenol (-10.17Kcal/mol) showed ACE higher inhibition activity than the standard drugs Captopril (-4.4Kcal/mol), Enalapril (-6.47Kcal/mol), Lisinopril (-8.68Kcal/mol) and Temocapril (-8.68Kcal/mol) were identified. All the 3 selected compounds showed interactions on the binding sites of the ACE. The identified compounds can be used for further research as potential drugs with higher inhibition and lesser side effects can be developed as alternatives to synthetic drugs.